Relationship between periodontal disease and triglycerides / cholesterol-HDL ratio in college students - Baez Duarte, Blanca Guadalupe; Cuamatzin García, Fernando; Zamora Ginez, Irma; Martínez Montaño, María del Lurdez Consuelo Martínez-Montaño; Limón Cerón, Juan Fernando Limón-Cerón; García Juárez, Ariana (Horizonte Sanitario, 2024)
Objective: To determine the relationship between periodontal disease (PD) and the triglycerides (TG)/ high-density lipoprotein cholesterol (HDL-C) ratio (as a marker of cardiovascular risk, CVR) in a population of Mexican college students. Materials and Methods: A descriptive, observational, cross-sectional and homodemic study was conducted with students from Faculty of Medicine at the Benemérita Universidad Autónoma de Puebla (BUAP). Demographic (age, sex), anthropometric (body mass index), biochemical (TG, HDL-C), and periodontal data were collected. Periodontal status was assessed using the Community Periodontal Index (CPI). Correlation tests were employed to analyze the relationship between the TG/HDL-C ratio and PD with statistical significance set at p ≤ 0.05. Results: A significant correlation between the TG/HDL-C ratio and CPI was found, even after adjusting for demographic, anthropometric, lifestyle and socioeconomic variables (rho = 0.344, p = 0.006). Conclusions: The PD was positively and significantly related with CVR in young people of 19.1 ± 1.3 years. Keywords: Community periodontal index; Triglycerides; Cholesterol HDL; College students.